Estimation of combustion flue gas acid dew point during heat recovery and efficiency gain - Bahadori, Alireza (Elsevier, 2011)
When cooling combustion flue gas for heat recovery and efficiency gain, the temperature must not be allowed to drop below the sulfur trioxide dew point. Below the SO3 dew point, very corrosive sulfuric acid forms and leads to operational hazards on metal surfaces. In the present work, simple-to-use predictive tool, which is easier than existing approaches, less complicated with fewer computations is formulated to arrive at an appropriate estimation of acid dew point during combustion flue gas cooling which depends on fuel type, sulfur content in fuel, and excess air levels. The resulting information can then be applied to estimate the acid dew point, for sulfur in various fuels up to 0.10 volume fraction in gas (0.10 mass fraction in liquid), excess air fractions up to 0.25, and elemental concentrations of carbon up to 3. The proposed predictive tool shows a very good agreement with the reported data wherein the average absolute deviation percent was found to be around 3.18%. This approach can be of immense practical value for engineers and scientists for a quick estimation of acid dew point during combustion flue gas cooling for heat recovery and efficiency gain for wide range of operating conditions without the necessity of any pilot plant setup and tedious experimental trials. In particular, process and combustion engineers would find the tool to be user friendly involving transparent calculations with no complex expressions for their applications.